Huisheng Oral Solution Adjunct With Platinum-Based Chemotherapy for the Treatment of Advanced Non–Small Cell Lung Cancer: A Meta-Analysis and Systematic Review - Huang, Jingyi; Wang, Zhichao; Xue, Han; Cao, Ailing; Turner, Cassidy; Wang, Jing; Zhang, Li; Wang, Jinghai; Xiao, Na; Xu, Jie; Zhou, Xianmei; He, Hailang (Frontiers in Pharmacology, 2020)
Background: Platinum-based chemotherapy is one of the first line therapies for the advanced non-small cell lung cancer (NSCLC), even though, its high toxicity and limited clinical effects cannot be neglected. Huisheng Oral Solution (HSOS) has been widely used as an adjutant chemotherapy drug for NSCLC in China. To systematically analyse the therapeutic effects of the combination of HSOS and platinum-based chemotherapy, a comprehensive meta-analysis was performed. Objectives: This systematic review and meta-analysis aimed to evaluate the effectiveness and safety of HSOS for NSCLC. Methods: The randomized controlled trials (RCTs) were selected on seven medical databases up to June 2020, including advanced NSCLC treatment using HSOS plus platinum-based chemotherapy versus chemotherapy alone. We followed the PRISMA checklist in general, applying Cochrane handbook 5.1.0, GRADE Pro GDT, RevMan 5.3, Stata12.0 and TSA 0.9.5.10 Beta to evaluate the quality of the study and analysis the data. Results: Based on Cochrane handbook 5.1.0, 15 RCTs consisting 1165 patients met the criteria and were selected for further analysis. Compared to chemotherapy alone, the chemotherapy combined with HSOS significantly improved objective tumor response (ORR) [RR = 1.38, 95% CI (1.19, 1.59), 𝑃 ˂ 0.0001], disease control rate (DCR) [RR = 1.10, 95% CI (1.04, 1.16), 𝑃 = 0.0006] and Karnofsky Performance Status (KPS) [RR = 1.79, 95% CI (1.41, 2.26), 𝑃 ˂ 0.00001]. But there was no evidence of improvement in the one-year survival rate [RR = 1.37, 95% CI (0.98, 1.92), 𝑃 = 0.07]. In terms of the side effects, HSOS administered concurrently with chemotherapy resulted in a serial of substantial benefits: lower toxicity to white blood cell [RR = 0.30, 95% CI (0.20, 0.43), 𝑃 < 0.00001], lower platelet toxicity [RR = 0.56, 95% CI (0.34, 0.92), 𝑃 = 0.02], and reduced incidence of vomiting [RR = 0.52, 95% CI (0.29, 0.92), 𝑃 = 0.03]. Conclusions: The meta-analysis indicated that HSOS plus platinum-based chemotherapy was more beneficial for patients, as the therapy could synergize antitumor activity and attenuate toxicity. The finding requires confirmation by further rigorously designed RCTs.